PRE DONATION DEFERRAL PATTERN AMONG BLOOD DONORS IN TERTIARY CARE HOSPITAL, AJMER, RAJASTHAN - MEENA, GOKUL CHAND; BEELWAL, DINESH; TAILOR, SHASHI BHUSHAN; SUNARIA, RAVI KANT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Analyze pattern of blood donor deferral in our hospital and provide safe and adequate blood and blood products to patients. Methods: A cross-sectional study on analysis of deferred donors of blood from January 2021 to December 2021 over 1 year was conducted in a zonal blood center in J.L.N. hospital, Ajmer. Results: During the study period, a total of 14104 blood donors were registered. Out of these, 13587 were males and 517 were females. Among males, 12,655 donated blood and 932 were deferred for several reasons. Among females, 341 donated blood and 176 were deferred. The total no of donors deferred was 1108. Real deferral rate was 7.85%. Conclusion: Donors who do not meet the selection criteria should be deferred on a temporary or permanent basis. All deferred donors should be treated with respect and care in a confidential manner and should be given a clear explanation of the reason for deferral and an opportunity to ask questions. Donors are less likely to return to donate blood if unclear or unsatisfactory information is given about the reason for deferral. Counseling of deferred blood donors could enhance the compliance of donors to seek follow-up medical care.